Intel : reinventing a technology brand - Shamdasani, Prem N. (London : SAGE Publications: SAGE Business Cases Originals, 2022)
Intel has become one of the world's largest semiconductor chip makers by revenue, and it is one of the most recognizable and valuable technology brands in the world. It became the dominant maker of microprocessors for PCs, notebooks, and servers through heavy investment in research and development, marketing, and branding. Given the growing demand for cloud, security, and datacentric solutions, Intel had to reorganize and focus on delivering processors, platforms, and technologies to power cloud computing and leverage on the Internet of Things, artificial intelligence, memory, 5G, and autonomous driving technologies, to enable companies to process, analyze, store, and transfer data. Intel's strategy was to transform from a PC-centric to a data-centric company and to provide end-to-end solutions for its customers in taking advantage of the data-rich environment.While this transformation created new business opportunities and growth for the company, it also created strategic and branding challenges for Intel as it endeavored to position itself as the market leader. How could Intel reinvent and reposition its brand to communicate that its technologies would drive products and services in an increasingly smart, connected, and data-driven world? Could Intel continue to leverage on its past and successful ingredient branding strategy? With the growing importance of its data-centric businesses, should Intel recalibrate its business-to-business-to-consumer branding strategy?
Includes bibliographical references and index.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Intel Corporation -- Case studies; Semiconductor industry -- Case studies; Branding (Marketing) -- Case studies